Design and synthesis of N-[6-(Substituted Aminoethylideneamino)-2-Hydroxyindan-1-yl]arylamides as selective and potent muscarinic M1 agonists. Issue 19 (1st October 2015) - Liu, Bin; Croy, Carrie H.; Hitchcock, Stephen A.; Allen, Jennifer R.; Rao, Zhigang; Evans, David; Bures, Mark G.; McKinzie, David L.; Watt, Marla Leigh; Stuart Gregory, G.; Hansen, Marvin M.; Hoogestraat, Paul J.; et al.
Graphical abstract